“Identificación de los parásitos gastrointestinales en el ganado bravo de páramo del sector Pansache retamales de la provincia de Cotopaxi” - Naranjo Carvajal, Allison Michelle (2023)
The present investigation was carried out in the sector of Pansache-Retamales, belonging to the parish of Juan Montalvo, which belongs to the canton Latacunga of the province of Cotopaxi, with the objective of identifying the gastrointestinal parasites present in the brave cattle and proposing a deworming protocol for the control and prevention of parasitosis. The methodology used was the collection of 50 samples of feces from cattle of different ages and sexes, directly from the rectum of the animals, through the introduction of the hand covered with a gynecological check-up glove, Each sample was identified and labeled with earring number and sex, The samples were transported at a temperature of 4°C in a refrigerated thermos flask for coproparasitological analysis at the veterinary clinical and microbiological laboratory "La quinta pata del gato" using the flotation technique with sugar solution. In this research, the results of the parasites, age, and sex of the cattle were analyzed. The female sex had the highest parasitic load of Moniezia, with a total of 17 infected animals, including Moniezia 14 infected animals (4.62%), Cooperi one infected animal (0.33 %), Ostertagia one infected animal (0. 33%), Fasciola one infected animal (0.33 %), with the male sex we have a total of 8 infected animals, Moniezia 4 infected animals (0.68 %), Cooperi 3 infected animals (0.61 %), Ostertagia one infected animal (0.17%), a sanitary deworming plan based on Praziquantel at a dose of 10 mg/kg bw, Abendazole at a dose of 5 mg/kg bw, Febendazole at a dose of 2 mg/kg bw, Doracmetin at a dose of 0.2 mg/kg bw via SC, Pyrantel 13 mg/kg bw, and Pyrantel 13 mg/kg bw.